Bending behaviour of dowelled mortise and tenon joints in Kempas / Rohana Hassan, Azmi Ibrahim and Zakiah Ahmad - Hassan, Rohana; Ibrahim, Azmi; Ahmad, Zakiah (Research Management Institute (RMI), 2008)
Mortise and tenon are commonly used as timber connections between beam and column with enhancement by pultruded dowel. At present the data on the performance of mortise and tenon joints manufactured using Malaysian tropical timber is not available. Therefore there is a need to provide such data for better guidance and references in design purposes. This study investigates the behavior and strength properties of dowelled mortise and tenon timber connections using selected Malaysian tropical timber with different types of dowels namely steel and timber. Bending tests were performed on mortise and tenon beam-column joints of Kempas when plugged with steel or wood dowel. It is found that pegging the connections with the respective steel and timber dowels resulted in a bending load capacity of 6.09 and 5.32 kN, taken as the average of three samples, the latter being 12 % lower than former. Visual observation of the failed test pieces revealed steel dowels exhibiting yield mode Im and wood, mode IIIs. The wood dowels yielded in bending at one plastic hinge point per shear plane with an associated wood crushing while the steel dowels remained practically undeformed with an associated crushing of the main member.